“Wetra”: Kearifan Lokal dalam Budidaya Tanaman Jagung di Desa Yaltubung Kecamatan Pulau-Pulau Babar - Matheos Rumahlewang; August E. Pattiselanno; Jeter D. Siwalette (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Wetra: Local Wisdom in corn cultivation in Yaltubung Village, Pulau-Pulau Babar District, Southwest Maluku Regency. Supervised by A.E. Pattiselano and D.J. Siwalette. Yaltubung Village is one of the villages in the Babar Islands sub-district, Southwest Maluku Regency which has wisdom in managing its local food. One of the local wisdoms of Yaltubung Village is called Wetra, namely corn. This study aims to identify the process of local wisdom in Wetra, to know the values of local craftsmanship in Wetra, to analyze the role of Wetra for the food availability of the people of Yaltubung Village, this study uses a qualitative descriptive analysis method. The results of this study indicate that Wetra as Local Wisdom is very good, Wetra as the staple food for the people of Yaltubung Village and to meet the food needs of the community.